Thirty-two-year trends of cancer incidence by sex and cancer site in the Veneto Region from 1987 to 2019 - Alessandra Buja; Giuseppe De Luca; Manuel Zorzi; Emanuela Bovo; Simone Mocellin; Simone Mocellin; Chiara Trevisiol; Vincenzo Bronte; Stefano Guzzinati; Massimo Rugge; Massimo Rugge (Frontiers Media S.A., 2024)
BackgroundThis observational study considers the sex-specific incidence of the most incident cancers as recorded in the population-based Veneto Regional Cancer Registry over a period of more than 30 years (1987-2019).MethodsThe Veneto Regional Cancer Registry collected data for the time interval 1987-2019. Significant changes in incidence trends calculated on age-standardized incidence rates (Annual Percent Change-APC) were identified by join point regression analysis.ResultsOverall, the incidence trend for all cancers decreased in males and remained stable in females. In nine cancer sites, the incidence trends showed consistent differences by sex (oral cavity, esophagus, colon rectum and anus, liver, larynx, lung, cutaneous malignant melanoma, bladder, and thyroid gland). Other malignancies did not show significant sex-related differences (stomach, pancreas, biliary tract, kidney/urinary tract, central nervous system, multiple myeloma, non-Hodgkin lymphoma, and leukemia).ConclusionIn the period 1987-2019, this study revealed sex-related differences in cancer incidence trends. Over time, cancer incidence remained higher in males, with a decreasing epidemiological impact, plausibly resulting from prevention campaigns against environmental cancer risk factors, as tobacco and alcohol. Conversely, a significant decrease was not observed in the incidence trend in females. These findings contribute essential insights for profiling the epidemiological map of cancer in a large Italian population, allowing comparison with other European cancer epidemiology studies and providing updated data supporting sex-related primary and secondary cancer prevention strategies.